STATUS REPRODUKSI DAN POTENSI SAPI SONOK DI KABUPATEN PAMEKASAN - S., Nurlaila; B., Kurnadi; M., Zali; H., Nining (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2018)
The method of data collection was done by interviewing farmers directly (respondents) using questionnaires. There were 4 subdistricts those were being the targets of the population, namely from 13 subdistricts in Pamekasan District were the locations for maintaining sonok cattle. Cluster proporsive sampling was determined by the sample of respondents, that was the method of sampling by setting characteristics those were in accordance with the objectives and criteria, namely all of the Sonok cattle those were kept by farmers in 4 subdistricts in Pamekasan District which were the centers for Sonok cattle breeding. The reproduction status of Sonok cattle in Pamekasan District was quite good. The first age of marriage was 23.40 ± 4.17, S / C 1.59 ± 0.53 times, the distance between young calf 14.50 ± 1.83 months, and the value of reproductive efficiency (ER) is 90.51%. The natural increase (NI) value of Sonok cattle in Pamekasan District in 2014 was 9.55%, the value of net replacement rate (NRR) was 101, 48%. The estimation result of Sonok cattle output was 8.24%. Madura cattle population dynamics at the Sonok cattle Nursery Center in Pamekasan District in the period of 2013 to 2017 experienced an average increase of 7.98% annually. The estimated results of the population dynamics from 2018 to 2022 were expected to increase annually by 9.18%. It was concluded that Sonok cattle in Pamekasan District still had the potential to increase the population and the output value was lower than NI (5.06% vs. 15.81%). Keywords : Pamekasan District, Reproduction Status, Natural Increase Value, Sonok Cattle, Questionnaire